MedECC 2020 summary for policymakers - Cramer, Wolfgang (2020)
Virtually all sub-regions of the Mediterranean Basin, on land and in the sea, are impacted by recent anthropogenic changes in the environment. The main drivers of change include climate (tempera-ture, precipitation, atmospheric circulation, extreme events, sea-level rise, sea water temperature, salinity and acidification), population increase, pollution, unsustainable land and sea use practices and non-indigenous species. In most areas, both natural ecosystems and human livelihoods are af-fected. Due to global and regional trends in the drivers, impacts will be exacerbated in the coming decades, especially if global warming exceeds 1.5 to 2°C above the pre-industrial level. Significantly enhanced efforts are needed in order to adapt to inevitable changes, mitigate change drivers and increase resilience.